The Impact of Agenda 2000's Structural Policy Reform on FDI in the EU - Fritz Breuss; Peter Egger; Michael Pfaffermayr (Austrian Institute of Economic Research (WIFO), 2001)
This paper analyses the effects of Agenda 2000's policy reform on the stocks of outward FDI to the European Union member countries. In a three-factors proximity-concentration New Trade Theory model we indentify the channels of influence on the FDI decision. In the empirical part, we estimate a dynamic panel data model and find that structural expenditures exert a significant positive impact on real stocks of outward FDI to EU countries. We simulate the Agenda 2000 program and obtain short-term and long-term effects of the EU country-specific changes in structural budgets on FDI to these countries.
Keywords: C33; F14; F15; 330; FDI; Gravity equation; European integration; Panel econometrics; Auslandsinvestition; EU-Strukturfonds; Neue Außenhandelstheorie; Gravitationsmodell; EU-Staaten